Peran Dan Fungsi Camat Setelah Menjadi SKPD (Satuan Kerja Perangkat Daerah) Studi Pada Kecamatan Pedurungan - LAILA NOVI NUZULIN NADA; Puji Astuti; Ahmad Taufiq (Journal of Politic and Government Studies, 2016)
ABSTRACT In accordance with Law no.32 of 2004 article 126 and further enforced by Government Regulation 19 of 2008, present day camat hold specific roles that are different from what their predecessors had. This research aims to discover the responsibilities and functions of camat after they are made as SKPD as well as the obstacles they have to face while performing assigned tasks.Qualitative descriptive analysis is used in this research, meaning that the study provides descriptions about relevant circumstances and events and/or ongoing processes. Descriptive method is intended as solving mechanism for the observed problems by depicting condition of research subject or object.From this research, it is found that the role of kecamatan officials is to run governmental, developmental, and societal affairs. Moreover, it is also found that factors deemed to have influence on the enforcement of camat's main responsibilities and functions are camat's leadership capacity, facilities and infrastructures, and regional budget. Obstacles that are discovered in this research is brittle relationship between Camat and society which causes misunderstandings in decision making and lack of manpower to effectively run the organization. Keywords: Camat, SKPD, Authority